Pengaruh Rasio Aktivitas dan Likuiditas Terhadap Profitabilitas Pada Perusahan Retail di BEI Tahun 2020-2023 - Lestari, Putu Dian; Ayu Purnamawati, I Gusti; Gede Erni Sulindawati, Ni Luh (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to examine the effect of activity and liquidity ratios on profitability in retail companies listed on the Indonesia Stock Exchange during the period of 2020 to 2023. The variables analyzed in this study include activity ratios, namely inventory turnover, total asset turnover, and working capital turnover, as well as liquidity measured by the current ratio as the independent variables. Profitability is projected using ROA as the dependent variable. The study employs multiple linear regression analysis to test the influence of these ratios on company profitability. The results show that, partially, inventory turnover has no significant effect on the profitability of retail companies, total asset turnover has a positive and significant effect, while working capital turnover and liquidity have a negative and significant effect on profitability. Simultaneously, all four variables have a positive and significant effect on the profitability of retail companies. These findings may serve as a consideration for management in managing activity and liquidity ratios to improve the company’s financial performance.